(untitled) (Research, Society and Development, 2022)
The traceability ensures the registration of information about the ’path’ that the food traveled from field production to the consumer’s table. The Anvisa, together with the Mapa , through INC No. 2, of 2018 and INC No. 1, of 2019, demanded the adaptation of producers to the procedures of traceability of vegetable products. However, when the food is produced by family farmers, considering in communities with low levels of education, lack of infrastructure and many without internet access, traceability becomes a major challenge. This article verified the adequacy of the family farmer to the traceability of the food production chain, through the application of a multiple case study. A survey was carried out with nine vegetable farms located in the Alto Tietê region, Brazil. The results showed that one producer implemented the traceability system, but to control only 1% of its total production, which serves large fast-food chains. Most producers have incomplete elementary education (55%), work practically alone in production and rely on the help of family members. The results also showed that producers are unable to carry out traceability due to the lack of registration of the inputs used in production, which makes implementation unfeasible even if the community has IT infrastructure. In this way, it considers that traceability is important for the food chain, but due to the lack of a legal structure for the inputs, added to the lack of technical assistance make it difficult for producers in Alto Tietê to comply to INC 01 of 2019.